Bank Capital and Operational Efficiency: A Cross-country Analysis of Asian Banking Sectors (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This study examines how the bank capital affects efficiency in Asian banking sector. This study used quantitative approach and explanatory research design. This study used both developed and developing 21 Asian countries as a sample covering the period from 2004 to 2021. These sample data were extracted from World Bank, 2023. This study employed ordinary least squares (OLS), fixed-effect, and random-effect estimators, and the findings revealed that bank capital increases efficiency and outcomes are robust in all three regression models. This finding also supports the efficient-structure hypothesis and stated that higher capital offers the opportunity to invest in cost-reducing modern technologies and processes that reduce cost and increase efficiency. Similarly, bank stability and private credit to GDP increase bank efficiency and this effect is consistent in all three models. In contrast, bank diversification and remittance inflows decrease bank efficiency in Asian countries. Policymakers can utilize these findings to implement stricter capital adequacy ratios, ensuring that banks maintain adequate capital to absorb losses and promote efficiency. In addition, policymaker should monitor recent diversification trends and penalize practices that compromise core banking efficiency.